In vitro evaluation of the antimicrobial and antioxidant properties of extracts from whole plant of Alternanthera pungens H.B. & K. and leaves of Combretum sericeum G. Don - Cheikna ZONGO; Aly SAVADOGO; Marius K. SOMDA; Jean KOUDOU; Alfred S. TRAORE (International Journal of Phytomedicine, 2011)
Resistance to current antimicrobial agents continues to increase and render difficult the fight against microbial diseases. There is an urgent need to find new disposable and affordable remedies to face this problem. Plants have been used for centuries for health cure and constitute an important source of drugs. In this study, the aqueous, water-ethanol, and water-acetone extracts of Alternanthera pungens H. B. & K. and Combretum sericeum G. Don were evaluated for antimicrobial and antioxidant activities. The antimicrobial activity was evaluated by disc diffusion and microdilution assays. Antioxidant Activity Index (AAI) was determined for antioxidant activity evaluation. The extracts from the leaves of C. sericeum exhibited potent antimicrobial activity. The highest inhibition zone diameters (IZD) were obtained with these extracts. The lowest minimum inhibitory concentration (MIC) (0.625 mg/ml) was recorded against Enterococcus faecalis for all the extracts from this plant and against Lysteria Monocytogenes for the water-acetone extract only. C. Sericeum showed also strong antioxidant activity with AAI comparable to standard antioxidant compounds such as Vitamin C and BHA. A. Pungens showed weak antimicrobial and antioxidant activities, comparatively to C. Sericeum. Phytochemical analyses showed also high total phenolic and total flavonoid contents in C. Sericeum extracts than in A. pungens. The use of these plants in traditional medicine is justified and they constitute a source for further investigations for traditional enhanced drug and active molecules discovery.